2011
DOI: 10.3762/bjnano.2.37
|View full text |Cite
|
Sign up to set email alerts
|

Formation of precise 2D Au particle arrays via thermally induced dewetting on pre-patterned substrates

Abstract: SummaryThe fabrication of precise 2D Au nanoparticle arrays over a large area is presented. The technique was based on pre-patterning of the substrate before the deposition of a thin Au film, and the creation of periodic particle arrays by subsequent dewetting induced by annealing. Two types of pre-patterned substrates were used: The first comprised an array of pyramidal pits and the second an array of circular holes. For the dewetting of Au films on the pyramidal pit substrate, the structural curvature-driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 44 publications
3
90
0
Order By: Relevance
“…On the other hand, however, above a critical thickness of the deposited AuPd film, the AuPd NPs show higher mean size (versus the film thickness) on substrate B than on substrate A, indicating that the AuPd film interacts with the substrate topography during the dewetting process. These results are quantified and discussed by the description of the substrate topography effect on the excess of chemical potential driving the dewetting process [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, however, above a critical thickness of the deposited AuPd film, the AuPd NPs show higher mean size (versus the film thickness) on substrate B than on substrate A, indicating that the AuPd film interacts with the substrate topography during the dewetting process. These results are quantified and discussed by the description of the substrate topography effect on the excess of chemical potential driving the dewetting process [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, generally, the dewetting of deposited thin metal films is analyzed on flat substrates [39][40][41][42][43][44][45][46][47]. However, some works demonstrated that specific intentional patterning of substrate Affects the spatial distribution and size of the NPs formed by the dewetting process of a deposited film [48][49][50][51]. The FTO layer that we use as substrate is un-intentionally patterned since it is formed by FTO pyramids randomly distributed on the glass slide as result of the deposition process of the same FTO layer [52,53], namely substrate A.…”
Section: Introductionmentioning
confidence: 99%
“…For polycrystalline metallic films, dewetting is also affected by the character of grain boundaries [89]. Concerning all effects above, dewetting of polycrystalline metallic films on a flat substrate usually leads to a broad distribution of particle size and spacing [90].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Therefore, it is important to control the thermal dewetting procedure. Previous studies [90,91] on the dewetting process of thin metal films show that the key parameters which can tune the particle size and density after thermal dewetting are the film thickness (h au ) , the dewetting temperature (T ann ), and the dewetting time (t ann ) . In order to understand how these three parameters influence the NWs growth results after the dewetting process, Gomes et al [92] …”
Section: Science China Materialsmentioning
confidence: 99%
“…The first method, based on the thermal dewetting of a gold layer, has already shown promising results on patterned substrates [18] and on one diatom species [10]. The second method involves the modification of the frustules surface using a coating of polyethylene glycol (PEG).…”
Section: Introductionmentioning
confidence: 99%